Implantable Doppler Probes for Postoperatively Monitoring Free Flaps: Efficacy. A Systematic Review and Meta-analysis. Issue 11 (November 2016) - Chang, Tzu-Yen; Lee, Yao-Chou; Lin, You-Cheng; Wong, Stanley Thian-Sze; Hsueh, Yuan-Yu; Kuo, Yao-Lung; Shieh, Shyh-Jou; Lee, Jing-Wei
Abstract : Background: Although clinical assessment remains the gold standard for monitoring the circulation of free flaps, several adjunct techniques promote timely salvage by detecting circulation compromise early. The objective of this systematic review was to evaluate the efficacy of an implantable Doppler probe for postoperatively monitoring free flaps. Materials and Methods: English-language articles evaluating the efficacy of implantable Doppler probes compared with clinical assessment for postoperatively monitoring free flaps were analyzed. The outcome measures were total flap failure rates, salvage rates, sensitivity, false-positive rates, and positive likelihood ratios. Results: Of the 504 citations identified, 6 comparative studies were included for meta-analysis. An implantable Doppler probe significantly lowered the flap failure rate (risk ratio: 0.40; 95% confidence interval: 0.21–0.75) and raised the successful salvage rate (risk ratio: 1.73; 95% confidence interval: 1.16–2.59). Pooled sensitivity was higher (1.00 vs 0.98), the positive likelihood ratio was lower (72.16 vs 220.48), and the false-positive rate was higher (0.01 vs 0) in the implantable Doppler probe group than in the clinical assessment group. Conclusion: An implantable Doppler probe is significantly more efficacious than clinical assessment for postoperatively monitoring free flaps.